Does A Capital Gains Tax Work? The Australian Experience Eleven Years On - Bentley, Duncan (Journal of Malaysian and Comparative Law, 2019)
Part I of this article looks at some of the major arguments that were put forward in Australia for and against the introduction of a capital gains ta. Part II examines design issues that affected its implementation. Part III considers aspects of the Australian experience since the introduction of a tax on capital gains, to determine whether the policy objectives were met. The article concludes by raising the issues that Malaysia should consider before following the majority of OECD and many other countries in introducing a comprehensive tax on capital gains.